Pengaruh Pendidikan Kewirausahaan, Locus of Control, dan Media Sosial Terhadap Minat Berwirausaha: Pada Siswa Kelas XI SMK Negeri 2 Singaraja - Ni Putu Yunika Dewi; Made Ary Meitriana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to determine the influence of entrepreneurship education, locus of control, and social media on entrepreneurial interest in grade XI students of SMK Negeri 2 Singaraja. The research method in this study is a quantitative research method with primary data obtained from questionnaire data measured using the Likert scale. The population of this study is grade XI students at SMK Negeri 2 Singaraja. The sample technique used is the proportionate stratified random sampling technique. The analysis technique used is multiple linear regression analysis with partial (t-test) and simultaneous (f-test) hypothesis tests. The results of this study show that (1). Entrepreneurship education has a positive and significant effect on students' interest in entrepreneurship which is shown by calculating the variables of entrepreneurship education of 9.717 > table 1.970 significance level 0.000 < 0.05, (2). The locus of control has a positive and significant effect on students' interest in entrepreneurship which is shown by the calculation of the entrepreneurship education variable of 14,898 > 1,970 table of significance level 0.000 < 0.05, (3). Social media has a positive and significant effect on students' interest in entrepreneurship which is shown by calculating the variables of entrepreneurship education of 15,530 > table 1,970 significance level 0.000 < 0.05, and (4). Entrepreneurship education, locus of control, and social media have a positive and significant effect on students' interest in entrepreneurship which is shown by the calculation of the variables of entrepreneurship education of 127.169 > Ftable 2.64 significance level 0.000 < 0.05.